The Role of Collaborative Leadership: A Case Study of the Eid Transportation Command Post at Hunimua Ferry Port, Indonesia - Fatubun, Salvius Osiyel (Populasi, 2025)
This study analyzes the role of collaborative leadership in the effectiveness of the 2025 Eid Transportation Post at Hunimua Ferry Port, Central Maluku. In the face of complex challenges such as high traffic volume, limited infrastructure, and cross-agency operational demands, this research adopts a qualitative embedded single case study design. Data was collected through in-depth interviews, direct observations, and institutional document analysis. Findings reveal that the success of the post is closely linked to leadership figures who perform three collaborative functions: steward (ensuring inclusive and transparent coordination), mediator (managing inter-agency relationships and resolving conflicts), and catalyst (driving adaptive innovation and cross-sector mobilization). These roles were effectively carried out by the Post Team Leader and the Post Manager, despite minimal institutional protocols. The prevailing leadership style identified was that of an organic leader, which fostered responsive coordination through informal networks. However, the absence of formal facilitation systems and integrated SOPs limits the institutionalization of collaboration. The study recommends the development of a hybrid leadership style that combines relational legitimacy with professional facilitation to ensure sustainable cross-agency coordination. This research contributes to the theoretical development of collaborative governance in the context of transport services and provides practical insights for institutional reform of temporary integrated command posts.